HIECS data: Measuring SDG's indicators for better policies - Amer, Nesma (2019)
As part of the seminar held by the International Food Policy Research Institute (IFPRI) in collaboration with UNDP "Measuring poverty and food security in Egypt: current state & the potential of big data"